2004
DOI: 10.2111/1551-5028(2004)057[0275:lgeogv]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term grazing effects on genetic variation in Idaho fescue

Abstract: The effect of cattle grazing on the genetic structure of native grass populations has received little attention. We investigated the effect of cattle grazing on genetic variation in Idaho fescue (Festuca idahoensis Elmer) using ISSR (inter-simple sequence repeat) DNA markers. The ISSR markers are hypervariable and are generally interpreted as being selectively neutral. Idaho fescue tillers were sampled from inside (N = 31) and outside (N = 34) a 64-year-old cattle exclosure in southeastern Oregon. We extracted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
(43 reference statements)
1
10
1
Order By: Relevance
“…Our study using controlled grazing intensities has eliminated the variability induced by the uncertainties in animal grazing intensity and by spatial heterogeneity in the natural environment. Contrary to our findings, some studies show that grazing has no impact on the genetic diversity of Festuca population (Matlaga and Karoly 2004;Mengli et al 2005), indicating grazing effects on the genetic diversity of plant population may differ among species.…”
Section: Population Of Stipa Species Show Rich Genetic Diversitycontrasting
confidence: 99%
See 1 more Smart Citation
“…Our study using controlled grazing intensities has eliminated the variability induced by the uncertainties in animal grazing intensity and by spatial heterogeneity in the natural environment. Contrary to our findings, some studies show that grazing has no impact on the genetic diversity of Festuca population (Matlaga and Karoly 2004;Mengli et al 2005), indicating grazing effects on the genetic diversity of plant population may differ among species.…”
Section: Population Of Stipa Species Show Rich Genetic Diversitycontrasting
confidence: 99%
“…A few studies on this issue have produced confounding conclusions. Some studies showed that long-term grazing did not reduce the genetic diversity of Festuca population (Matlaga and Karoly 2004;Mengli et al 2005), whereas others found that grazing reduced the genetic diversity of populations of Kobresia pygmaea and Stipa species (Shan et al 2006;Liu et al 2009a). The objective of present study is to elucidate whether the small-scale grazing disturbance affects the genetic diversity of plant populations in the Inner Mongolia grassland.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many previous studies showed that the ungrazed individuals were not significantly genetically differentiated from the grazed individuals based on molecular marker analysis. [ 71 , 72 ]. Therefore, the grazing avoidance mechanism is codetermined by environmental conditions and genetics with the genetic variation most likely to be at an epigenetic level [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of grazing effects in grazed populations have focused more on morphological, physiological, and reproductive adaptations (e.g., Caldwell et al 1981;Hodgkinson and Williams 1983;Kalkner and Casler 2000), and less on genetic variability and structure of grass populations (Carman and Briske 1985;Tomá s et al 2000;Matlaga and Karoly 2004). Recently, Matlaga and Karoly (2004) found no genetic difference between grazed and protected populations of Festuca idahoensis Elmer using ISSR (intersimple sequence repeat) DNA markers. However, a preliminary RAPD (random amplified polymorphic DNA) analysis with F. campestris, which is a much more grazing-sensitive species (Willms et al 1985), seemed to suggest there were significant changes in gene frequencies due to grazing (W. Willms, unpublished data, 2004).…”
Section: Introductionmentioning
confidence: 99%